All about fibromyalgia - Wallace, Daniel J. (Daniel Jeffrey), 1949- (Oxford University Press, 2002)
This is a thoroughly revised and updated version of ""Making Sense of Fibromyalgia"", endorsed by the Arthritis Foundation. This new volume continues to provide a comprehensive guide - for both patients and professionals - to this little-known and poorly understood syndrome